Quantitative Analysis of Caffeine Levels in Local Coffee (Coffea sp) Powder on Dabo Island with UV-Vis Spectrophotometry - Sri Hainil; Suhaera Suhaera; Lirtri Lirtri (Borneo Journal of Pharmacy, 2019)
Coffee (Coffea sp) is the second-largest beverage consumed by people around the world whose process comes from the processing and extraction of coffee beans. Coffee has a chemical compound, one of which is caffeine. Caffeine is a crystal-shaped compound. Caffeine can be a tangible white powder or a shiny white needle-shaped, odorless caffeine, and caffeine has a bitter taste. The purpose of the study was to determine the caffeine levels of local ground coffee on the island of Dabo with the spectrophotometry UV-Vis method. Analysis of the ground coffee caffeine levels is quantitative determined using spectrophotometry UV-Vis. The equation of the calibration curve of caffeine is regression y = 0.1307x + 0.0112 with a correlation coefficient value (r) of 0.9993. Based on Indonesian National Standards (SNI) 01-7152-2006, The maximum limit of caffeine in foods and beverages is 150 mg/day and 50 mg/serving. The results of the analysis of caffeine levels from three samples of ground coffee circulating on Dabo Island each in 2 g were 0.3383 mg for Sample A; 0.3786 mg for Sample B; and 0.5803 mg for Sample C.